The Effect of Nurse Therapeutic Communication on the Level of Anxiety of Patients' Families in the Intensive Care Unit (ICU) Room of the Hospital. Prof. Dr. H. Aloei Saboe - Fitria Kadir Thalib; Pipin Yunus; Rosmin Ilham (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
The Intensive Care Unit (ICU) is a special treatment area in the hospital that is used to treat patients who require stricter observation and is equipped with special medical equipment to help with the treatment and recovery of patients. This study aims to determine the effect of nurses' therapeutic communication on the level of anxiety of patients' families in the ICU room of Prof. Dr. H. Aloei Saboe Hospital. This study is a quantitative approach research with a one group pre-post test design. This study showed that the patient's family anxiety before therapeutic communication in the ICU of Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City, was obtained by the patient's family who had a very severe level of anxiety, namely 24 people (53.3%). And as many as 21 people (46.7%) had severe levels of anxiety. The patient's family's anxiety after therapeutic communication measures were carried out in the ICU of Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City, was obtained by the families of patients who had a mild anxiety level, namely 31 people (68.9%). And as many as 14 people (31.1%) had moderate levels of anxiety. There was an effect of nurses' therapeutic communication on the patient's family anxiety level in the ICU of Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City.There was a significant influence where using a paired t-test on the value p = 0.000. (p<0.05).